Graft-induced Recovery of Inhibitory Avoidance Conditioning in Striatal Lesioned Rats is Related to Choline Acetyltransferase Activity. (1994) - Piña, Ana Luisa; Ormsby, Christopher Edward; Miranda, María Isabel; Jiménez, Nicolás; Tapia, Ricardo; Bermúdez-Rattoni, Federico
Abstract : Four groups of male Wistar rats showing disrupted inhibitory avoidance conditioning due to striatal lesions received either striatal or ventral mesencephalic brain grafts. Two additional non-lesioned groups were used as controls. Half of the groups was retrained in an inhibitory avoidance task at fifteen days postgraft and the other half at sixty days postgraft. Those animals receiving striatal grafts significantly improved their ability to acquire the inhibitory avoidance task at fifteen and sixty days postgraft, as opposed to those receiving mesencephalic grafts, which did not show behavioral recovery. Choline acetyltransferase and glutamate decarboxylase activities, as well as dopamine content, were measured in the grafted tissue. Striatal grafts showed levels of choline acetyltransferase activity similar to the control group. Moreover, a positive correlation was found between the choline acetyltransferase activity and the behavioral recovery. In contrast, both glutamate decarboxylase activity and dopamine levels were significantly lower in striatal and in mesencephalic grafts, as compared to the controls. These results show that striatal but not mesencephalic grafts can promote the restoration of the ability to acquire an inhibitory avoidance task even at early stages (15 days) of the development of the grafts. The results also suggest that acetylcholine plays an important role in behavioral recovery.